(The Process of Pyrolization Bamboo Throuugh Direct Combustion by using Fire Brick Kiln) - Pohan, H.G; Maman Rohaman, M (Balai Besar Industri Agro, 2008)
The study on effect of bamboo variety and pyrolization through direct combustion using a fire brick klin model wquiped with a condenser to produce charcoal and vinegar has been carried out. The observation was conducted on the time and temperature profile of pyrolization process, yield of charcoal and its collected vinegar. The resulted charcoal and its liquor were subjected to further analysis, i.e. ash content, volatile matter at 950C, fixed carbon content, and calorific value for the charcoal and the pH, organic subtances profile for the liquor. The study revealed that the yield of charcoal was varied from the lowest 8. 07 % (wb) of Bamboo Petung and the highest of 20.81% (wb)i.e., of Bamboo Andong. The ash content of charcoal was varied from 5.01 to 6.8% (wb). The volatile matter at 950C was varied from 17.47 to 33.96% (wb) whereas the fixed carbon content was ranged from 5237 to 6637 cal/g. The electrica! conductivity was ranged from 8 - >9 , degree of crystallite between 10,45 and 14,51 % and surface area was ranged from 41,9 to 118,5 cm/g. it is also revealed yhat the yield of the Bamboo vinegar was varied from 6,52 - 17,26 % (wb) with pH varied from 3.75 to 4.01. The content of organic compounds found in liquor was varied i.e,. 19 compounds found in the liquor of Bamboo Andong, with dominant compound of tricyclo(2.2.2.1.0(2,6)heptene, 1,7 -dimetyhl-7-(4-methyl-3-penthyl)-(CAS)Si which comprised to 29.69 %, 29 compounds in liquor of Bamboo Petung with dominant compound of Acetic acid (CAS) Ethylic acid which comprised to 40.66 %, 13 compounds in liquor of Bamboo Ampel with domonant compounds of 2,6,10,14,18,22-Tetracosahexaene, 2,6,10,15,19,23,-hexamethyl- (CAS) Squ which comprised to 73.38 %; 39 compounds in liquor of bamboo Tali with dominant compound of cyclohexanon, 2-Isobutyl which comprised to 18.64% and 64 compounds was detected in liqour of bamboo Hitam domonant compounds of 2,3-dihydro-Ben zofuran which comprised to 11.53 %